Bioaccessibility In Vitro of Nutraceuticals from Bark of Selected Salix Species. (17th February 2014) - Gawlik-Dziki, Urszula; Sugier, Danuta; Dziki, Dariusz; Sugier, Piotr
Abstract : The aim of this study was to investigate and to compare the extractability, bioaccessibility, and bioavailability in vitro of antioxidative compounds from bark of selected Salix species: S. alba (SA), S. daphnoides (SD), S. purpurea (SP), and S. daphnoides x purpurea (SDP) hybrid willow clones originating from their natural habitats and cultivated on the sandy soil. The highest amount of phenolic glycosides was found in the bark of SDP and SD . The best source of phenolics was bark of SDP . The highest content of flavonoids were found in SD bark samples, whereas the highest concentration of bioaccessible and bioavailable phenolic acids was determined in SDP bark. Bark of all tested Salix species showed significant antiradical activity. This properties are strongly dependent on extraction system and genetic factors. Regardless of Salix genotypes, the lowest chelating power was found for chemically-extractable compounds. Bark of all Salix species contained ethanol-extractable compounds with reducing ability. Besides this, high bioaccessibility and bioavailability in vitro of Salix bark phytochemicals were found. Obtained results indicate that extracts from bark tested Salix genotypes can provide health promoting benefits to the consumers; however, this problem requires further study.